THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND QUALITY OF LIFE AMONG ELDERLY INDIVIDUALS WITH HYPERTENSION IN PEMBUANG HULU - Tasalim, Rian; Wijaksono, Muhammad Arief; Rahman, Subhannur; Suhaibah, Umi (HEARTY, 2026)
The elderly are a vulnerable age group prone to various degenerative diseases, one of which is hypertension. Uncontrolled hypertension can lead to a decline in the quality of life of the elderly, both physically, psychologically, socially, and environmentally. Family support plays an important role in maintaining the well-being of the elderly through emotional, instrumental, informational, and evaluative assistance. This study aims to determine the relationship between family support and the quality of life of elderly individuals with hypertension in the working area of Pembuang Hulu Public Health Center, Seruyan Regency, Central Kalimantan. This research employed a quantitative method with a descriptive-analytic approach and a cross-sectional design. A total sample of 30 elderly individuals with hypertension was selected using purposive sampling. The instruments used were a family support questionnaire and the WHOQOL-BREF to assess quality of life. Data analysis was performed using the Spearman correlation test. The results showed that most respondents (60%) received low family support, and the majority had a moderate quality of life (63.3%). The Spearman correlation test indicated a very strong and significant relationship between family support and quality of life (r = 0.916; p = 0.000). The conclusion of this study is that there is a significant relationship between family support and the quality of life of elderly individuals with hypertension. Therefore, increasing the role of the family in elderly care is highly recommended, especially in providing continuous support to improve the quality of life in rural areas.